Assessment of feed resources availability and use for cattle and pigs in Mai Son District, Son La Province, Vietnam - Tran, Thi Bich Ngoc; Nguyen, Thien Truong Giang; Hoang, Xuan Thao; Dao, Thi Thu Hang; Nguyen, Thi Minh Phuong; Triana Ángel, Natalia; Peters, Michael; Duncan, Alan J.; Atieno, Mary (International Center for Tropical Agriculture, 2023)
Son La province has recently put in place policies and programs to support expansion of livestock production, however the province still faces low livestock productivity due to low quality and availability of forages and feedstuff. One of the provincial government’s priorities is to increase productivity of cattle and pigs through improved animal nutrition practices such as increased cultivation of improved forages and better feed management and utilization. Using the Gendered Feed Assessment Tool (G-FEAST), this study assessed the availability and use of local feed resources, and identified feed gaps, challenges and constraints affecting livestock production to inform the design of context-specific and inclusive feed intervention strategies. The study was carried out in four villages in Hat Lot and Co Noi communes, Mai Son district, Son La province, Vietnam. Gender-disaggregated data was collected from 16 focus group discussions (FGDs) (eight FGDs with women and eight FGDs with men) and 49 individual interviews (23 women and 26 men). Winter feed shortage was reported as the most pressing challenge. Further constraints included low yield and/or nutritive value of local forages varieties (mainly Napier). The poor quality of diets arising from use of high proportion of crop residues such as rice bran, banana trunk and sugarcane tops was also flagged as a challenge. Men tend to be engaged in activities such as preparing land, planting forage, harvesting, and purchasing, while women are more engaged in cleaning of feeding points, watering, and weeding. The results present key opportunities and entry points for gender-responsive locally suited feed intervention strategies that can address these context-specific challenges, mainly winter feed shortage, can greatly improve livestock productivity and efficiency. Such interventions include capacity building of women and men farmers, extension & vet staff on utilization of locally available feed resources and purchased feeds, feed conservation, diet formulation, and feeding regimes, and promoting improved forage varieties (establishment, management, and utilization), for cattle and pigs.